2014
DOI: 10.1073/pnas.1216063110
|View full text |Cite
|
Sign up to set email alerts
|

Biogeography of time partitioning in mammals

Abstract: Many animals regulate their activity over a 24-h sleep-wake cycle, concentrating their peak periods of activity to coincide with the hours of daylight, darkness, or twilight, or using different periods of light and darkness in more complex ways. These behavioral differences, which are in themselves functional traits, are associated with suites of physiological and morphological adaptations with implications for the ecological roles of species. The biogeography of diel time partitioning is, however, poorly unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
209
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 253 publications
(238 citation statements)
references
References 57 publications
6
209
0
4
Order By: Relevance
“…They have driven the development of biological phenomena from the molecule to the ecosystem, including metabolic and physiological pathways, the behaviour of individuals, geographical patterns of adaptation and species richness, and ecosystem cycles (e.g. [1][2][3][4]). Indeed, biological systems are arguably organized foremost by light [5][6][7].…”
Section: The Challengementioning
confidence: 99%
“…They have driven the development of biological phenomena from the molecule to the ecosystem, including metabolic and physiological pathways, the behaviour of individuals, geographical patterns of adaptation and species richness, and ecosystem cycles (e.g. [1][2][3][4]). Indeed, biological systems are arguably organized foremost by light [5][6][7].…”
Section: The Challengementioning
confidence: 99%
“…[27,[65][66][67][68]). Comparative studies have discussed transitions between nocturnality and diurnality, and have suggested that mammals have undergone a 'nocturnal bottleneck' during evolution to escape predation [69,70].…”
Section: (B) Ecologymentioning
confidence: 99%
“…Depending on the constraints of physiological thermal limit and light availability, animals evolved few basic patterns of diel activity: diurnal, nocturnal, crepuscular or cathemeral (Bennie et al 2014). In mammals, a given animal can stably and predictably switch back and forth between different patterns in context-dependent ways (Kas and Edgar 1999;Mrosovsky 2003).…”
Section: Network Architecture Under Ld Cyclesmentioning
confidence: 99%